Metodologia badań Wincentego Stysia - Kowalczyk, Edyta (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2014)
Wincenty Styś hailed from the academic circles of Lviv. He applied a historical research method, which comprised a detailed description of economic processes, as well as the social changes that accompanied them. Styś represented an interdisciplinary research approach and opposed the isolation of economic activity from other areas of social life. He considered the influence of political, legal and historical relations on the economy while specializing in agricultural economics. From this perspective, he analyzed systemic transformations in rural areas and the influence of population processes on agricultural lands. Furthermore, Styś held that the findings of historical research lead to the discovery of economic laws. Meanwhile, his research was characterized by meticulous and laborourious empirical studies that formed the basis for formulating original scientific hypotheses.
Keywords: Styś, Wincenty (1903-1960); ekonomia; metoda badawcza; szkoła historyczna (ekonomia)